2019
DOI: 10.4236/nm.2019.102009
|View full text |Cite
|
Sign up to set email alerts
|

Affective Behavior Dysregulation Was Induced by Chronic Administration of Copper in Wistar Rats

Abstract: As both deficiency and excess of copper (Cu) can be harmful, dysregulation in its homeostasis has been connected with various neurological disorders. The present study was undertaken to examine whether Cu chronic administration can induce alterations of affective behavior especially anxiety and depression levels in male and female rats. Twenty-four rats, for each gender, divided in control and three test groups (n = 6), were injected intraperitoneally with saline (0.9% NaCl) or CuCl 2 (0.25 mg/kg, 0.5 mg/kg an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…A significant association between Cu and neurobehavioral performance was revealed [17][18][19]. Our previous data have demonstrated that chronic Cu exposure modulates affective behaviors [20].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A significant association between Cu and neurobehavioral performance was revealed [17][18][19]. Our previous data have demonstrated that chronic Cu exposure modulates affective behaviors [20].…”
Section: Introductionmentioning
confidence: 83%
“…Group IV: animals were administered Copper (1 mg/kg) once daily. The concentrations of Cu used in this study were chosen based on our previous experiment evaluating neurobehavioral alterations in rat [20].…”
Section: Animals and Experimental Conditionsmentioning
confidence: 99%
“…Our previous study showed that chronic Ni exposure induced depression-like, anxiety-like, memory deficit, and alterations in OS markers in the hippocampus [13], a crucial brain region in learning, memory processes, and emotion regulation [14,15]. These effects are similar to those induced by other heavy metals such as Copper(Cu), Cadmium(Cd) and Aluminum(Al) [16][17][18][19]. Certain…”
Section: Introductionmentioning
confidence: 90%
“…A luminum (Al) neurotoxicity is a major factor influencing affective and cognitive disorders (Zghari et al, 2018). A growing body of literature suggests that heavy metals, including cadmium, copper and nickel, produce affective and cognitive disorders in rat brain (Lamtai et al, 2018(Lamtai et al, , 2019(Lamtai et al, , 2020a(Lamtai et al, , b, 2021El-Brouzi et al, 2020). Neurodegenerative diseases such as Alzheimer's disease (AD) have also been linked to Al exposure (Esparza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%